Low-emission Rice Market Creation through Public-Private Partnerships and Evidence-based Decision-making - International Rice Research Institute (2025)
Public-Private Partnerships (PPPs) are a powerful tool for transforming rice production, especially when creating a market for low-emission rice, which is otherwise identical to traditional rice. These partnerships act as a formal platform for key players to offer strategic input on government policy, share lessons learned, and address technical and financial gaps. The success of these collaborations depends on high-level, long-term commitment from various organizations, including the International Rice Research Institute (IRRI). For IRRI, participation in these PPPs provides a crucial role in shaping the enabling environment for sustainable rice without always leading to direct funding or publications. This allows IRRI to leverage its position as a trusted partner to directly influence high-level discussions on market creation and demand. Ultimately, these partnerships give organizations like IRRI a direct line to provide valuable, formal input at the country level.